Where There's Fire, THere's Smoke: Air Quality and Prescribed Burning in Florida - Martha C. Monroe; Austin K. Dixon; David R. Godwin; Adam C. Watts; Leda N. Kobziar (EDIS)
Prescribed burning, the carefully planned and directed use of fire to achieve land management goals, is a useful tool for natural resource managers in Florida. Landowners may choose fire to achieve a variety of objectives, including restoring fire-dependent ecosystems, enhancing forage for cattle, improving wildlife habitat, preparing sites for reforestation, and reducing hazardous fuel loads. Prescribed burns achieve many benefits for the environment and for people, but they have the potential to impact the public via smoke. Smoke production is simply unavoidable with prescribed burning, but its potential to harm can be reduced with the use of smoke management techniques. Intended for land managers and the public, this document provides some background information on air quality, the effects of smoke on human health and safety, and some strategies that can be used to protect air quality.